Impact of steric factors on enzymatic resolution of 2,3-dihydro-1H-indenols taking into account the Koshland effect - Prysiazhnuk, D.V.; Kolodiazhna, A.O.; Kolodiazhnyi, O.I. (Reports of the National Academy of Sciences of Ukraine, 2023)
Enantiomerically pure 2,3-dihydro-1H-indendiols containing a hydroxyl group in the aromatic ring were obtained in high yields by enzymatic kinetic resolution of the corresponding racemates. Optimization of the process of deracemization was achieved by selecting biocatalysts, acylating reagents, solvents, and temperature, as well as the introduction of sterically bulky silyl substituents into the aromatic ring. The introduction of bulky tert-butyldimethylsilyl groups into the aromatic ring leads to an increase in the efficiency of deracemization and an increase in the ee of reaction products. For kinetic separation, both enzymatic transesterification and enzymatic hydrolysis of the corresponding acetates were used. As a result, dihydroindenediols with (S)- and (R)-absolute configurations of high enantiomeric purity were obtained. After the process of kinetic resolution, the enantiomeric purity of the products attained 99 % ee.